PENGARUH MEDIA MAPTILER TERHADAP HASIL BELAJAR DAN KREATIVITAS BERDASARKAN MOTIVASI BELAJAR GEOGRAFI MATERI PETA KELAS X.E1 DI SMAN 2 BATANG ANAI - Putri Andini; Bayu Wijayanto; Yurni Suasti; Lailatur Rahmi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the effect of using Maptiler digital learning media on learning outcomes and creativity in terms of geography learning motivation on map material in class X.E1 of SMAN 2 Batang Anai. The background of this study is based on the low learning outcomes and creativity as well as student motivation in geography learning due to the dominance of monotonous conventional methods and the minimal use of technology-based media. The research method used is a quasi-experimental design with a non-equivalent control group design. The research sample consisted of two classes, namely the experimental class (using Maptiler media) and the control class (using conventional media), each consisting of 30 students. The instruments used included pretest and posttest tests to measure learning outcomes, learning motivation questionnaires, and assignments to measure student creativity. The results showed that the use of Maptiler media had a significant effect on improving student learning outcomes. The results of the study showed that Maptiler media influenced student learning outcomes with a significance level of 0.000 <0.05, as indicated by a higher average posttest score in the experimental class and an N-Gain value of 60.82, which is categorized as quite effective. Thus, Maptiler media has been proven to significantly improve geography learning outcomes. Furthermore, there was a significant influence of the media, as evidenced by a sig. 0.000 <0.05, indicating a significant difference in media use. Meanwhile, there was no interaction between motivation, as evidenced by a sig. 192 >0.05. Similarly, there was no significant difference between the interaction between media and motivation on learning outcomes, as the sig. 893 exceeded 0.05. This indicates that the media's influence on learning outcomes is consistent and unaffected by student motivation.